Using blogs to support participative learning in university courses. (8th September 2009) - Agostini, Alessandra; De Michelis, Giorgio; Loregian, Marco
In this paper, we present our experience with a blog as support for our design-oriented courses at the University of Milano-Bicocca, Italy. The experience has been very satisfactory, showing a quantitative and qualitative improvement in students' participation in the learning experience. By adopting the consolidated viewpoints of Computer-Supported Cooperative Work (CSCW) and Communities of Practice (CoPs) researches to interpret the results of our experience, we aim to underline the appropriateness of blogs and their most relevant features in supporting collaborative, participative learning.